PENGARUH KREDIBILITAS INFLUENCER, KUALITAS KONTEN, DAN ENGAGEMENT TERHADAP KEPUTUSAN PEMBELIAN PADA MEREK SOMETHINC - Adhidarma, Keisya Gabriella; kiky, andreas (Jurnal Nusa Manajemen, 2025)
In the digital era, the use of social media influencers has evolved into a highly effective marketing strategy for influencing consumer purchasing behavior. This study selected Somethinc, a local skincare merek that has successfully achieved the highest sales rankings in Indonesia, as the focus of analysis. The main objective of the research is to evaluate the extent to which influencer credibility, content quality, and engagement levels affect consumers’ purchasing decisions for Somethinc products. A quantitative approach was employed through a survey method, distributing questionnaires to 150 respondents residing in the Greater Jakarta area (Jabodetabek). Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The research findings indicate that the three independent variables (influencer credibility, content quality, and engagement) collectively contribute to purchasing decisions. Furthermore, partial analysis revealed that each variable also has a significant individual impact. These results emphasize that implementing a well-planned influencer marketing strategy, with a focus on credibility, engaging content presentation, and intensive audience interaction, is essential in shaping consumer purchasing decisions. Therefore, this study is expected to serve as a reference for developing digital marketing strategies in the beauty industry, particularly for local mereks in Indonesia.